Comprehensive study of rapid capacity fade in prismatic Li-ion cells with flexible packaging - Zuzana Stravova; Ondrej Klvac; Jiri Bana; Bihag Anothumakkool; Tomas Zikmund; Pavel Blazek; Jozef Kaiser; Tomas Kazda (Scientific Reports)
Abstract Prismatic lithium-ion batteries (LIBs) are considered promising electric energy sources in electromobility applications due to their efficient space utilization. However, their sensitivity to external and internal influences and reduced durability lead to inflation risk and potential explosions throughout their lifecycle. These critical processes are strongly influenced by the inner construction of the cell, especially concerning the coating and mechanical fixation. This study subjects a commercially available prismatic LIB cell to comprehensive, correlative analysis employing various imaging techniques. The inner structure of the entire cell is visualized non-destructively by X-ray computed tomography (CT), enabling the identification of critical design flaws prior to electrochemical cycling. Electrochemical cycling simulates the battery lifecycle, and the cell is subsequently disassembled in the fully charged state. The usage of the inert-gas transfer system allowed the preparation of Broad Ion Beam (BIB) electrodes cross-sections in a fully native state and for the first time to observe the tearing of graphite particles due to over-lithiation. Established region labeling system allowed to use CT and scanning electron microscopy (SEM) correlatively to identify critical regions. After 100 cycles, a 40% capacity loss was observed and event diagram describing deagradation mechanisms, related both to the cell design and to the processes occurring at high load, was created.